Serviços ecossistêmicos e sua importância para a dinâmica e conservação do Pampa: uma análise da categoria familiar na fronteira Sant’Ana do Livramento/BR e Rivera/UY - Tatiane Almeida Netto; Roberto Verdum (Confins)
The globalization process since the end of the 20th century has brought about a new industrial logic, guiding the agricultural sector of the Pampa with the presence of transnational agro-industrial companies, changing the economic, social, cultural, local and regional structures, increasing the areas of crop reconversion like: soy, corn, rice and exotic trees. In this context, this research aims to describe the importance of family farming in a process of preservation and maintenance of native countryside areas, considering the historical and social transformations, the interactions and the agrarian dynamics. Methodologically, we used instruments such as documentary, bibliographic research, direct observation and semi-structured interviews with qualified informants in protected areas and around the Ibirapuitã/BR environmental protection area and in Valle del Lunarejo/UY by using the dialectic method and the qualitative approach for data analysis. This study considers the importance of family farming for the preservation and conservation of the Pampa, as well as the maintenance of ecosystem services, like provision, regulation, cultural and support for rural development. As a result, the adoption of new strategies of social reproduction is pointed out, such as the multifunctionality that is directed towards the improvement in the generation of colonial products and rural tourism, which are the most adopted strategies today. The remaining native pastures are linked to family animal husbandry and it is up to the social subject who develops it the decision to preserve the native field, therefore, public policies are needed for the recognition and valorization of this field, this agricultural practice and the ecosystem of the Pampa.